pengungkapan kegembiraan pada anak 3-5 tahun dalam kajian psikolinguistik - etin pujihastuti; rochwidjatini rochwidjatini; bambang lelono; sri nani hariyanti (Jurnal Lingua Idea, 2017)
In a psycholinguistic study, children at the age of 3-5 years old are considered at a differentiation period. In this period, children have already acquired their mother tongue, in terms of adult’s basic grammatical laws. The language which function as a means of communication starts working. Their vocabularies are quantitatively and qualitatively growing as their perceptions and experiences upon the world start to share with others including their expressions of feelings, in this case, their hillarious expression disclosure. However, in this period, children have not completely acquired adults’ linguistic structures. Thus, it is that estimated there are some differences between children’s hilarious expression structural dislosure and adults’. In addition, hilarious expression structural incompleteness may result in adults’ error perceptions on what the children mean. Based on data analysis, it is shown that children at the age of 3-5 years old have already aquired various linguistic aspects on hilarious expressions, including phonological, morphological, and syntactical aspects. one factor encouraging children to show their hilarious expressions is achievement, such as when accepted as a friend, given a gift/surprise, finding something, and feeling capable of doing something.